2018
DOI: 10.21834/jabs.v3i11.323
|View full text |Cite
|
Sign up to set email alerts
|

University Students' Knowledge, Attitude, And Perception of Risk related to HIV

Abstract: The number of young people aged between 13 to 29 infected with Human Immunodeficiency Virus (HIV) was rapidly increasing in Malaysia. The objective of this study is to determine the level of knowledge, attitude, and perception among students in the University. This study employed the cross-sectional design. The questionnaire was distributed to 372 respondents. Therefore, 52.4 percent of students had good knowledge.  There was a weak positive correlation between KA (r =0.23) and KP (r=0.19)  with signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The data collection was conducted by distributing the questionnaire. The research were used questionnaire adopted from Said [6]. The questionnaire was translated into Indonesian, and pilot tests were conducted on ten students outside the research subjects.…”
Section: Research Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…The data collection was conducted by distributing the questionnaire. The research were used questionnaire adopted from Said [6]. The questionnaire was translated into Indonesian, and pilot tests were conducted on ten students outside the research subjects.…”
Section: Research Instrumentmentioning
confidence: 99%
“…Most of the people with adequate knowledge will protect themselves better from getting a virus. Lack of knowledge can form a negative attitude towards people living with HIV [6]. People who have enough knowledge about risk factors, transmission, prevention, and treatment of HIV/AIDS tend not to be afraid and do not give stigma to people infected with HIV/AIDS [5].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been observed that students from countries, where the HIV prevalence is low, have a sense of false security and believe that they do not come in contact with people living with HIV (PLHIV) [ 8 ]. It seems that a lack of information and awareness about HIV infection make most young adults negligent about the true problem of HIV transmission and their individual risk [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%